Despite the genetic variability: NS1 of different dengue serotypes has comparable affinity for various host protein in silico - Jadoon Khan; Khalid Amin; Hayat Khan; Sadia Butt; Junaid Ahmad; Zafar Abbass Shah; Shubana Hayat; Ajaz Ahmad; Neelma Hassan; Amin Ullah (Journal of King Saud University: Science, 2024)
Background and Aim: Dengue infection is a global issue which is caused by insect transmitted, positive sense single-stranded RNA dengue virus (DENV). Around 50 million cases of dengue infection is being reported per year whereas population at risk of dengue of infection reaches about 2.5 billion in the tropical and subtropical regions of the world. The present study aimed to develop global consensus sequence of dengue NS1 protein and modelling interaction of NS1 with various host proteins of different cellular pathways. Methods: Serotype specific consensus sequences of Dengue NS1 were generated using CLC-Work Bench software. The Consensus sequences of NS1 and Cellular proteins were modelled using Protein Model Portal (PMP). Comparative interaction of NS1 of various dengue serotypes were analyzed by means of Haddock server. The biomolecular complexes of dengue NS1 and various host proteins (PTBP1, NF-kB, TRAF6, PAIP1, SRFBP1, FGB, TCF7L2 and EIF4G1) thus formed were evaluated for interacting residues through Protein Interaction Calculator (PIC). Results: The serotype-specific consensus sequences revealed high degree of conservation among the various NS1 domains of different isolates of same serotype but is more heterogeneous among different serotypes. The docking results demonstrated that most of the host proteins including (PTBP1, NF-kB, TRAF6, PAIP1, SRFBP1, FGB, TCF7L2 and EIF4G1) have comparable affinity for the NS1 of different serotypes despite considerable degree of variability among the serotypes. Analysis of interactive residues demonstrated involvement of different domains of NS1 for interaction with host partners even within the NS1 of different serotypes for a particular host protein. Conclusion: The in silico study revealed that various NS1 domains of different isolates were relatively conserved among different serotypes but highly heterogeneous from serotype to serotypes. The Wing domain of NS1 protein plays a vital role in interaction with the host proteins.